Hubungan Pengetahuan Dan Dukungan Keluarga Instrumental Dengan Kualitas Hidup Penderita Hipertensi Dewasa Pertengahan - Ni Made Jinarta Yani; Bagus Suryantara; I Made Rai Mahardika (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2026)
Abstract Introduction: Hypertension is a chronic disease that frequently affects middle-aged adults (45–59 years old) and can decrease their quality of life if not managed properly. The level of knowledge regarding hypertension and instrumental family support play an important role in helping patients undergo treatment and maintain their quality of life. This study aims to determine the relationship between knowledge level and instrumental family support with the quality of life among middle-aged hypertensive patients in the working area of Tabanan I Community Health Center. Objective: To determine the simultaneous relationship of knowledge level and instrumental family support with the quality of life of middle-aged hypertensive in the working area of Tabanan I Community Health Center Method: This study utilized a quantitative approach with a descriptive correlational design and a cross-sectional method. The sample was selected using a purposive sampling technique, involving 96 respondents Results: There was a significant relationship between knowledge level and instrumental family support with the quality of life of hypertensive patients(p = 0,000). nstrumental family support was the more dominant factor compared to knowledge level, with an odds ratio OR = 3,848, meaning that respondents with high instrumental family support were 3,848 times more likely to have a high quality of life Conclusion: Knowledge level and instrumental family support are significantly related to quality of life, where respondents with high family support have a greater likelihood of enjoying a better quality of life.